Experiment and Forward Modeling Analysis of Microgravity Detection of Urban Underground Space - Han LU; Yan SUN; Mingxia ZHOU; Chong ZHANG; Jiuyang YIN; Dong MA; Mingfei CUI; Hong JIANG (CT Lilun yu yingyong yanjiu, 2022)
With the rapid development of national cities, the demand for urban underground space exploration development and utilization has increased. Due to the interference factors in human activities areas, traditional geophysical methods can't obtain true and accurate detection data. The microgravity method is relatively less affected by interference factors. The interference from urban buildings and human activities can be eliminated by the method of model forward correction, so as to obtain high-precision gravity collection data, and then the spatial location information of tunnel, goaf, cavity, collapse area and pipe gallery in urban underground space can be obtained through effective inversion method. In this paper, through experimental detection and analysis of the theoretically affected factors in the urban detection carried out by the ground mobile high-precision gravity measuring instrument, combined with the forward model correction research, the microgravity method shows good effect in the detection of urban underground space.